Effects of antibiotic treatment and phagocyte infiltration on development of Pseudomonas aeruginosa biofilm—Insights from the application of a novel PF hydrogel model in vitro and in vivo - Wu, Hong; Song, Lulu; Yam, Joey Kuok Hoong; Plotkin, Marian; Wang, Hengzhuang; Rybtke, Morten; Seliktar, Dror; Kofidis, Theodoros; Høiby, Niels; Tolker-Nielsen, Tim; Song, Zhijun; Givskov, Michael (Frontiers in Cellular and Infection Microbiology, 2022)
Background and purpose Bacterial biofilm infections are major health issues as the infections are highly tolerant to antibiotics and host immune defenses. Appropriate biofilm models are important to develop and improve to make progress in future biofilm research. Here, we investigated the ability of PF hydrogel material to facilitate the development and study of Pseudomonas aeruginosa biofilms in vitro and in vivo. Methods Wild-type P. aeruginosa PAO1 bacteria were embedded in PF hydrogel situated in vitro or in vivo, and the following aspects were investigated: 1) biofilm development; 2) host immune response and its effect on the bacteria; and 3) efficacy of antibiotic treatment. Results Microscopy demonstrated that P. aeruginosa developed typical biofilms inside the PF hydrogels in vitro and in mouse peritoneal cavities where the PF hydrogels were infiltrated excessively by polymorphonuclear leukocytes (PMNs). The bacteria remained at a level of 106 colony-forming unit (CFU)/hydrogel for 7 days, indicating that the PMNs could not eradicate the biofilm bacteria. β-Lactam or aminoglycoside mono treatment at 64× minimal inhibitory concentration (MIC) killed all bacteria in day 0 in vitro biofilms, but not in day 1 and older biofilms, even at a concentration of 256× MIC. Combination treatment with the antibiotics at 256× MIC completely killed the bacteria in day 1 in vitro biofilms, and combination treatment in most of the cases showed significantly better bactericidal effects than monotherapies. However, in the case of the established in vivo biofilms, the mono and combination antibiotic treatments did not efficiently kill the bacteria. Conclusion Our results indicate that the bacteria formed typical biofilms in PF hydrogel in vitro and in vivo and that the biofilm bacteria were tolerant against antibiotics and host immunity. The PF hydrogel biofilm model is simple and easy to fabricate and highly reproducible with various application possibilities. We conclude that the PF hydrogel biofilm model is a new platform that will facilitate progress in future biofilm investigations, as well as studies of the efficacy of new potential medicine against biofilm infections.